Karakterisasi Limbah Medis dan Bed Material Pasir Silika pada Fluidized Bed Combustion - Rexcy Sanderan, Olan; Suprapta Winaya, I Nyoman; Lokantara, I Putu (Teknik Desain Mekanika; Vol 10 No 2 (2021): April 2021 : Teknik Desain Mekanika, 2021)
Abstract Currently, medical waste is a problem that must be handled immediately. The current increase in the volume of medical waste is also caused by the Covid-19 pandemic which is still happening today. Medical waste can be reduced in various ways, one of which is combustion with fluidized bed (FBC) technology. The size of bed material diameter is an indicator in the combustion process because it affects the fluidization process in the combustion chamber. This research was conducted using an experimental study approach that looked for the characteristics of medical waste and silica sand bed material in fluidized bed combustion. The bed diameter of the silica sand material will be varied with sizes 0.2 mm, 0.5 mm, 0.8 m, and 1.1 mm. Based on the tests that have been done, the best combustion process occurs at a diameter of 0.2 mm. This is because the smaller bed material can fluidize better so that the temperature of the combustion chamber can be evenly distributed. Keywords: Medical Waste, Silica Sand, Combustion, Fluidized Bed